What Drives Millennials' and Gen Z's Intentions to Participate in Cash Waqf Linked Sukuk? Perspectives from Islamic Altruism - Reyhanmulky, Muhammad; Supriani, Indri; Al-Ghifary, Muhammad Syauqy (Universitas Muhammadiyah Yogyakarta, 2024)
Waqf, in its conceptual essence, has the potential to enhance social and economic mobility, thus alleviating poverty. Nevertheless, the effective collection of waqf faces numerous challenges, particularly in adapting to the needs of Millennials and Generation Z. The objective of this research attempt is to examine how Islamic altruism moderates the impact of crucial determinants of cash waqf linked sukuk (CWLS) on fund collection. By employing the Structural Equation Model-Partial Least Squares (SEM-PLS) method, data were collected from 283 respondents belonging to the Indonesian millennial and Gen Z demographics via a self-structured questionnaire. The results emphasize that Islamic altruism does not play a substantial role in moderating the determinants of CWLS among the economic variables associated with Islam. Regarding domain-based economic decisions, individual contributions to CWLS are not reliably moderated by Islamic altruism. Despite adhering to the waqf principle, Islamic altruism, which entails the voluntary provision of assistance to others without personal gain, does not exert any influence on economic motivations for participating in CWLS. Furthermore, this research indicates that income level, religiosity, sharia financial literacy, and a strong inclination towards CWLS significantly influence the intention of Millennials and Generation Z to participate. Indonesia, being a Muslim-majority nation, could potentially witness significant progress in the field of financial waqf, specifically in the area of CWLS. The research's practical implications offer significant insights and direction for stakeholders, aiding in the formulation of efficacious policies and initiatives that promote CWLS fundraising among Millennials and Generation Z. This is novel research, and from the perspective of Islamic altruism theory, there has been a dearth of studies examining the critical factors that determine individual contribution in CWLS.